Survey on Fractals: An overview of fractals and their dynamics (Journal of Advances and Scholarly Researches in Allied Education, 2019)
From last years, fractals and the study of their dynamics is one of the emerging and attractive areas for mathematicians. A Fractal is a geometric shape each part of which has the same characteristics as the original one. By zooming a fractal, one can find that the patterns and shapes will continue repeating, forever. In this paper, I present a brief survey on fractals.